2015
DOI: 10.1001/jamadermatol.2014.4495
|View full text |Cite
|
Sign up to set email alerts
|

Medical Professional Liability Claims for Mohs Micrographic Surgery From 1989 to 2011

Abstract: The most common lawsuits pertaining to Mohs surgery list non-Mohs surgeons as the primary defendants. Closer coordination between non-Mohs surgeons and Mohs surgeons may help minimize risk to both parties and lead to better patient care. Small sample size is the primary limitation, in part owing to exclusion of out-of-court settlements from the database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…"Teach back" methods have been validated as successful ways to assess patient understanding of material recently presented [31]. With informed consent being the number one reason for litigation associated with common dermatological procedures, dermatologists may wish to spend additional time counseling patients preoperatively [32].…”
Section: Discussionmentioning
confidence: 99%
“…"Teach back" methods have been validated as successful ways to assess patient understanding of material recently presented [31]. With informed consent being the number one reason for litigation associated with common dermatological procedures, dermatologists may wish to spend additional time counseling patients preoperatively [32].…”
Section: Discussionmentioning
confidence: 99%
“…Using previously described methodologies, we performed a search of the LexisNexis legal case database between January 15 and February 15, 2021, for all publicly reported cases from federal and state courts. A reported case includes any judicial action of a court, including judgments, rulings, opinions, dismissals, or other official actions.…”
Section: Methodsmentioning
confidence: 99%
“…23 A large proportion of cases that led to malpractice litigation occurred in the face, head, and/or neck; this finding reflects the increased incidence of KC on sunexposed areas and the cosmetic importance of facial health and appearance, which may lead to an increased likelihood of malpractice litigation for KCs that affect the face. 5,24,25 We identified more than 15 specialties involved in malpractice litigation involving KCs and found significant differences in monetary payout by health care professional specialty in cases won by the plaintiff. Although more nondermatologists are performing dermatologic procedures, increased risk of litigation has previously been associated with laser surgery by nonphysician operators compared with dermatologists.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 80 cases of malpractice litigation involving melanoma 4 found that melanoma malpractice litigation involves numerous specialties (including dermatology, pathology, family medicine, and surgical specialties) and that approximately half of melanoma malpractice cases resulted in financial settlement. In addition, a 2015 analysis of 42 malpractice claims for Mohs micrographic surgery 5 found only 1 case in favor of the plaintiff.…”
mentioning
confidence: 99%